Adequacy of elderly dependent clothing: User's comfort and caregiver's handling facilities - Caldas, Artemísia (2015)
OBJECTIVE The elder population is increasing as a result of today’s quality of life. In particular the elderly dependent suffer with the available standard clothing, lacking in providing solutions to their specific needs. Simultaneously, caregivers handling is also challenged everyday when looking after them. This research is part of a PhD project which aims to analyze the anatomical shape of the elderly dependent of care, quantifying their measurements, shape and posture, compensating asymmetries, considering their limitations, including clothing requirements of comfort and associated factors, like functionality and handling.